PENERAPAN MODEL PEMBELAJARAN MATEMATIKA REALISTIK INDONESIA ( PMRI ) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SD NEGERI 008 SUNGAI SEGAJAH KECAMATAN KUBU KABUPATEN ROKAN HILIR - Wargini Wargini '; Lazim N Lazim N '; Zulkifli Zulkifli ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract : This research is motivated by lowmathematics learning outcomes ofstudents, with a grade average of 58.67. While the completeness criteria Minimumvalue (KKM) Mathematics is 65 Among students who are 32 people only 14students who achieve KKM with classical completeness of 43.7%. This research isClassroom Action Research (CAR) conducted aims to improve learning outcomesMathematics Elementary School fifth grade students Segajah 008 River byapplying learning model Realistic Mathematics Indonesia. Data collectioninstruments in this thesis is the sheet activities of teachers and students andlearning outcomes. This thesis presents the results obtained by studying theaverage learning outcome measures 58.67 before rising 15.63% to 67.83 in cycleI. In the second cycle increased by 23.58% to an average of 72.50. activities ofteachers in the first cycle the first meeting of the percentage obtained 60% withhigh category, the second meeting had become 75%. Furthermore, the firstmeeting of the second cycle teachers activity scores increased 85% with very highcategory, at the second meeting increased to 90% with very high category. Theresults of the data analysis of student activity in the first cycle to 65% with highcategory, 70% in the second meeting the students already understand this cycle oflearning activities with PMRI application. And the second cycle activity scoreincreased to 80% of students with very high category. At the second meetingincreased to 85% with very high category. The results of the study at 008 RiverElementary School fifth grade Segajah prove that the application of mathematicallearning model realistic Indonesia can improve learning outcomes Math 008 fifthgrade students of SDN Segajah River.Keywords: Realistic Mathematics Approach, Mathematics Learning Outcomes